2014
DOI: 10.11591/.v3i3.4692
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Immunization Defaulting among Children Age 12-23 Months in Hawassa Zuria District of Southern Ethiopia: Community Based Unmatched Case Control Study

Abstract: As part of the overall package of maternal and child health services in Ethiopia, all children are provided with free immunization services and it is available in all government health facilities, both in rural and urban areas. But significant number of children was defaulted from Immunization schedule, even after the health extension program was launched. Therefore, the study was assessed predictors of immunization defaulting among children age range of 12-23 months, in Hawassa Zuria district of southern Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
4
5
0
Order By: Relevance
“…Mothers who have poor knowledge about childhood immunization were four times more likely to default from completion of child immunization than those of mothers with satisfactory knowledge. This is consistent with a study conducted in a different part of Ethiopia and a study from Nigeria that both showed that maternal knowledge about child immunization has an independent and significant association with completion of child immunization [ 13 , 15 , 17 , 18 , 19 , 29 ]. Lack of access to information and knowledge about, by whom, where, and when children should be vaccinated were significantly associated with defaulting from completion of children vaccinated [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mothers who have poor knowledge about childhood immunization were four times more likely to default from completion of child immunization than those of mothers with satisfactory knowledge. This is consistent with a study conducted in a different part of Ethiopia and a study from Nigeria that both showed that maternal knowledge about child immunization has an independent and significant association with completion of child immunization [ 13 , 15 , 17 , 18 , 19 , 29 ]. Lack of access to information and knowledge about, by whom, where, and when children should be vaccinated were significantly associated with defaulting from completion of children vaccinated [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…We computed the sample size by considering the predictor variables from previous case-control studies conducted in Ethiopia [ 18 , 19 ]. Maternal knowledge of the vaccination schedule was selected since it gave the maximum sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Among sociodemographic factors, place of birth and type of residence were found to be independent factors that lead to incomplete immunization status of the child. Similar to our study, home delivery was found to be a risk factor in case-controlstudies carried out in Ethiopia [ 26 , 27 ]. The studies in a similar circumstance in India [ 21 ] and among migrant children in China [ 28 ] also supported the finding.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to the descriptive study carried out in India [ 21 ]. A recent case-controlstudy carried out in Ethiopia [ 26 ] also showed that maternal immunization-related knowledge was one of the significant predictors of immunization defaulting. The possible explanation could be that if the caretakers have the knowledge about the schedule of the vaccination, they immunize the children on time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the same source highlights the presence of significant regional variations in vaccine coverage. Existing studies of child immunization in the developing countries are primarily quantitative with a focus on the magnitude and completion rates, than others [ 4 , 8 - 12 ]. Moreover, while immunization of children might be affected by several factors, its identification using qualitative evidence collected from children's caretakers is generally minimal and narrow addressing aspects of the possible factors, often based on global reviews [ 13 - 17 ].…”
Section: Introductionmentioning
confidence: 99%